DNA Interaction and DNA Cleavage Studies of a New Platinum(II) Complex Containing Aliphatic and Aromatic Dinitrogen Ligands - Nahid Shahabadi; Soheila Kashanian; Maryam Mahdavi; Noorkaram Sourinejad (Bioinorganic Chemistry and Applications)
A new Pt(II) complex, [Pt(DIP)(LL)](NO3)2 (in which DIP is 4,7-diphenyl-1,10-phenanthroline and LL is the aliphatic dinitrogen ligand, N,N-dimethyl-trimethylenediamine), was synthesized and characterized using different physico-chemical methods. The interaction of this complex with calf thymus DNA (CT-DNA) was investigated by absorption, emission, circular dichroism (CD), and viscosity measurements. The complex binds to CT-DNA in an intercalative mode. The calculated binding constant, Kb, was 6.6×104 M−1. The enthalpy and entropy changes of the reaction between the complex and CT-DNA showed that the van der Waals interactions and hydrogen bonds are the main forces in the interaction with CT-DNA. In addition, CD study showed that phenanthroline ligand insert between the base pair stack of double helical structure of DNA. It is remarkable that this complex has the ability to cleave the supercoiled plasmid.